State reduction in a dependent demand inventory model given by a time series - Reyman, Grzegorz (European journal of operational research, 1989)
The dependent demand inventory model given by the time series with a stochastic trend and seasonality was considered. A two-state variable dynamic programming problem was reduced to the one-state variable problem under linear cost structure. The demand distribution was shown to be normal with the nonstationary mean and the constant variance. The optimal ordering levels are characterized by single critical numbers.